Práticas de consumo das redes sociais por mães de vítimas do incêndio da boate Kiss: a criação de experiências no cotidiano - Pavanello, Alice Bianchini (2019)
This dissertation has as central problem to understand the role of consumer online social networking practices for mothers of victims of the fire of Kiss Nithclube in the creation of experiences in the daily life, in order to restructure the afterlife tragic death of a child. It started from the idea that digital cultures provided the emergence of a new form of communication as well as a series of experiences in the different social dimensions, as well as allowing the emergence of spaces for old practices such as those related to mourning and death (ELIAS, 2001, RODRIGUES, José, 2006). Thus, we want to understand the particularities and singularities of the online practices of this group of women. The tragedy of Kiss Nithclube left 242 dead in January 2013 at Santa Maria, Rio Grande do Sul. Even though the police investigation pointed out several irregularities in the nightclub, until February 2019, no one had been held criminally responsible for the killings. Moved by a feeling of helplessness, mothers activate communicative and social dynamics to unite the maternal figure, associated with the domestic space (BADINTER, 1985), in the image of warriors who occupy public spaces (VIANNA, FARIA, 2011) to fight for justice and by the memory of children and tragedy, while seeking ways to re-inhabit the world (Das, 1996). As a theoretical basis, the sociocultural perspective of consumption (DOUGLAS, ISHERWOOD, 2004; MILLER, 2007; MILLER et al 2016) is adopted as something representative and symbolic, capable of giving meaning and identity to the practices and processes of groups and individuals (BARBOSA; CAMPBELL, 2012) in social networks. It starts from the idea of the internet as a cultural artifact, incorporated into everyday life (HINE, 2004, 2015), which assumes different meanings depending on the context in which it is consumed. In this research, an ethnographic approach to the Internet (HINE, 2015) is applied with fieldwork, which includes observation of publications on social networking sites, interactions in offline environments, and interviews with four mothers of victims. It is concluded that the struggle for justice and memory has assumed a centrality in the lives of these mothers that permeates all instances, as well as online social networks, especially Facebook. Thus, their online consumption practices are experienced to build a space of action where they can talk about their pains and their demands, can maintain the image of a mother who suffers and who fights for a collective cause and for a change in the society, besides experiencing mourning and longing. It is also concluded that Facebook assumes five central meanings in the life of mothers: resistance, protection, therapeutic, memory and a new way of being a mother.